The Influence of Brand Reputation and Brand Experience on Consumer Loyalty Towards Viva Brand Cosmetics In ambon city - Huwae, Victor Ernest; Pelupessy, Merry M; Siahainenia, Silfiena (Sean Institute, 2025)
This study aims to determine the effect of brand reputation and brand experience on consumer loyalty to Viva brand cosmetic products in Ambon City. The research method used is a quantitative approach with a survey technique. The research sample was 150 female respondents aged 25–65 years who use Viva products. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results showed that brand reputation and brand experience have a positive and significant effect on consumer loyalty. This finding emphasizes the importance of building a good brand image and creating a positive experience for consumers in increasing loyalty to Viva cosmetic products.